The Long-Tailed Monkey (Macaca fascicularis) Food Preferences In The Mount Pengsong Area - Rifcka Aulia Hidayati; Muhlis Muhlis; M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
This study aims to know the type and food preference for the long-tailed monkey (Macaca fascicularis) in the Gunung Pengsong area. Data were collected using the observation method by direct observation at certain predetermined points consisting at the forest area around the settlement of Kuranji Village. This research was analyzed descriptively and qualitatively. The results of the research on the type of food Macaca fascicularis found in the forest area of ​​Mount Pengsong as many as 28 plant species, while around the settlement of Kuranji Village as many as 17 plant species. The preference of Macaca fascicularis in the forest area of Mount Pengsong was obtained as many as 5 plant species consisting of Ficus benjamina 15.2%, Syzygium cumini 11.9%, Durio zibethinus 7.3%, Bambusa vulgaris 6.7% and Syzygium aqueum 6.6%, while the preference of Macaca fascicularis around the settlement of Kuranji Village was obtained as many as 9 plant species consisting of Muntingia calabura 17,5%, Moringa oleifera 12,4%, Syzygium cumini 11,3%, Nephelium lappaceum 10,3%, Ficus carica 8.9%, Mangifera indica 8%, Syzygium aqueum 7,9%, Ficus benjamina 6.8% and Manilkara kauki 5.7%.